A review on green supply chain aspects and practices - Islam, Shamimul; Karia, Noorliza; Ahmad Fauzi, Firdaus; Mohamed Soliman, Mohamed Soliman (De Gruyter Open, 2017)
The field of green supply chain is expanding rapidly, and new authors are venturing in this field to conduct further research. Although some literature reviews have beeen conducted over time, a complete list of green supply chain practices is not available. Hence, the objective of this study is to present an up-to-date list of green supply chain practices. To achieve this, the study employed structured review process, as well as critically examined the contents to ensure that the data are filtered from high-quality peer-reviewed journals and from influential authors in this field. 91 highquality papers were selected from top ten journals in GSCM area to produce the list. A total of 58 green supply chain practices comprising 15 aspects were featured, e.g. reverse logistics, industrial symbiosis, green information technology, green design, carbon management etc. This paper contributes to the existing literature by providing a comprehensive list of aspects and practices of the green supply chain. Finally, limitations and directions for future studies are provided in the conclusion section.